Study of photocatalytic response of MWCNTs decorated PbS nanocrystals. (2022) - Sahu, Rajesh; Manjhu, Suchitra; Malhotra, Anu; Sharma, K.B.; Jain, S.K.; Tripathi, Balram
Abstract: Multi-walled carbon nanotubes (MWCNTs) dispersed lead sulphide (PbS) nanophoto catalyst synthesized by the chemical method. Surface engineering of MWCNTs decorated with PbS nanocrystals (NCs) is a very effective tool for the conversion of chemical energy into solar energy. In this study prepared samples of MWCNTs/PbS nanocomposites show well distinct photocatalytic behaviour under visible light by the degradation of methylene blue (MB) dye. This study demonstrates that organic dye methylene blue degrades (more than 95%) in MWCNTs/PbS nanocomposites within 120 min under visible light irradiation. The distribution in crystalline size of PbS NCs and MWCNTs/PbS nanocomposites is 22.79 nm and 12.38 nm, respectively. Reducing crystalline size in MWCNTs/PbS nanocomposites indicate the formation of a good photo catalyst and represents excellent co-catalysts for the photocatalytic process. MWCNTs as co-catalysts increases the reaction rate and reduces photo corrosion of the photo catalyst after adsorption on the surface of PbS NCs.